A Study on the Complexity of a New Chaotic Financial System. (10th October 2020) - Liao, Yi; Zhou, Yiran; Xu, Fei; Shu, Xiao-Bao
Abstract : The interaction of elements in a financial system can exhibit complex dynamic behaviours. In this article, we use a system of differential equations to model the evolution of a financial system and study its complexity. Numerical simulations show that the system exhibits a variety of rich dynamic behaviours, including chaos. Bifurcation diagrams show that the system behaves chaotically over a wide range of system parameters.